Response of Pinus merkusii Jung. & Devr. Megagametophyte Explants Cultured on DCR Medium with Different 2,4-D and Kinetin Combination - Nabila, Afini Zulafa; Rahmat, Adi; Kusdianti, Kusdianti; Yulianty, Nurfitri (-, 2024)
Pinus merkusii Jung. Devr. is a multipurpose tree species that is widely cultivated for timber, resin production, and land conservation. Nearly all parts of the tree are utilized, making it highly valuable. However, the high demand for its products is not met by its low natural regenerative capacity, which poses challenges for sustainable management. To address this, somatic embryogenesis, an in vitro propagation technique, has been explored as an alternative method for multiplying conifer species like Pinus merkusii. This study aims to assess the in vitro response of megagametophyte explants cultured on DCR medium with various combinations of 2,4-D and kinetin. The concentrations of 2,4-D tested were 0 µM, 7 µM, 9 µM, and 11 µM, while kinetin was tested at 0 µM, 2 µM, 3 µM, and 4 µM. The explants used were megagametophytes from female strobili measuring 5-7 cm, containing young zygotic embryos in the preembryo stage. After two months of cultivation in the dark, the explants exhibited responses such as enlargement, callus formation, and germination. The highest response rates for explant enlargement, callus formation, and germination were observed in the combinations of DK00 and DK04 (33.33%), DK70 and DK114 (33.33%), and DK72 and DK114 (44.44%). No somatic embryo formation was observed, possibly due to the age of the explants.